Drug-conjugated PLA–PEG–PLA copolymers: a novel approach for controlled delivery of hydrophilic drugs by micelle formation. (17th November 2017) - Danafar, H.; Rostamizadeh, K.; Davaran, S.; Hamidi, M.
Abstract: A conjugate of the antihypertensive drug, lisinopril, with triblock poly(lactic acid)–poly(ethylene glycol)–poly(lactic acid) (PLA–PEG–PLA) copolymer was synthesized by the reaction of PLA–PEG–PLA copolymer with lisinopril in the presence of dicyclohexylcarbodiimide and dimethylaminopyridine. The conjugated copolymer was characterized in vitro by hydrogen nuclear magnetic resonance (HNMR), Fourier transform infrared (FTIR), differential scanning calorimetry (DSC) and gel permeation chromatography (GPC) techniques. Then, the lisinopril conjugated PLA–PEG–PLA were self-assembled into micelles in aqueous solution. The resulting micelles were characterized further by various techniques such as dynamic light scattering (DLS) and atomic force microscopy (AFM). The results revealed that the micelles formed by the lisinopril-conjugated PLA–PEG–PLA have spherical structure with the average size of 162 nm. The release behavior of conjugated copolymer, micelles and micelles physically loaded by lisinopril were compared in different media. In vitro release study showed that in contrast to physically loaded micelles, the release rate of micelles consisted of the conjugated copolymer was dependent on pH of media where it was higher at lower pH compared to the neutral medium. Another feature of the conjugated micelles was their more sustained release profile compared to the lisinopril-conjugated copolymer and physically loaded micelles.